2010
DOI: 10.1183/09031936.00089510
|View full text |Cite
|
Sign up to set email alerts
|

Time interval to conversion of interferon-  release assay after exposure to tuberculosis

et al.

Abstract: The proper interval for repeating an interferon-c release assay (IGRA) among tuberculosis contacts with initially negative results is unknown. The interval for IGRA conversion after exposure to patients with active pulmonary tuberculosis in an outbreak setting was evaluated.In a platoon of 32 soldiers, four active pulmonary tuberculosis patients, in addition to one index patient, were diagnosed during a contact investigation. For the other 27 contacts, a tuberculin skin test (TST) and QuantiFERON1 TB-Gold In-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 17 publications
2
35
0
3
Order By: Relevance
“…In fact, although all subjects were, by definition, TST-negative at enrollment, both groups already had evidence of Mtb-sensitization by WB-IGRA. This observation re-enforces early reports that a detectable delayed-type sensitivity reaction resulting in a positive TST forms 2–10 weeks following primary infection with Mtb [30], and contributes to an emerging literature exploring time to IGRA conversion following known Mtb exposure [31]. Notably, we observed that at initial TST conversion, those who would go on to revert their TST following INH treatment had no significant changes in Mtb-specific T cell IFN-γ responses compared to their enrollment, pre-TST conversion, values.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, although all subjects were, by definition, TST-negative at enrollment, both groups already had evidence of Mtb-sensitization by WB-IGRA. This observation re-enforces early reports that a detectable delayed-type sensitivity reaction resulting in a positive TST forms 2–10 weeks following primary infection with Mtb [30], and contributes to an emerging literature exploring time to IGRA conversion following known Mtb exposure [31]. Notably, we observed that at initial TST conversion, those who would go on to revert their TST following INH treatment had no significant changes in Mtb-specific T cell IFN-γ responses compared to their enrollment, pre-TST conversion, values.…”
Section: Discussionsupporting
confidence: 85%
“…The conversion of TST usually occurs about two to 12 weeks after infection and the T. SPOT.TB between four and 22 weeks [18]. In one patient (#13), T. SPOT.TB presented a positive result prior to TST conversion and, at least in this case, T. SPOT.TB was sensitive enough to identify LTBI in advance.…”
Section: Discussionmentioning
confidence: 99%
“…The discordance may, in part, be due to delayed conversion of IGRAs relative to TST as suggested by other recent findings such as a TB outbreak in a military camp in South Korea where PTB contacts were systematically tested with QuantiFERON ® -TB Gold in-tube (QFT-GIT) at various time points after the start of the investigation. QFT-GIT conversions were observed between 4 and 22 weeks, suggesting that IGRAs may have a broad and at times lengthy window period for conversion [86]. During a contact investigation in Spain, agreement between TST and QFT-GIT, and correlation with intensity of Mtb exposure, improved after the tuberculin window period which is generally accepted as two months [87].…”
Section: Shortcomings Of Igra Testingmentioning
confidence: 94%